Estructura del diagrama H-R y función de luminosidad del cúmulo abierto NGC 2547 - Clariá Olmedo, Juan José (1982)
Results from new UBV - DDO photometry as well as spectroscopic and kinematical data of stars in NGC 2547 are presented and discussed. Contrary to the result found by Fernie, the present photometry does not show any evidence of a cluster pre-main sequence. A minimum binary frequency of 58 %, a mean distance of (450±45) pc and other fundamental parameters are derived. A gap of Δ(B-V) ∼ 0.08 in the main sequence distribution of stars has been detected between spectral types A3 and A7. This gap, probably due to the abrupt of several open clusters having ages nearly similar to that of NGC 2547. The luminosity function of the bright members agrees very well with that averaged over 62 clusters given by T_{eff}.